Credit management in Ukrainian agro- industrial complex in modern management conditions (Economics and region, 2016)
In the article the state of crediting of enterprises of agroindustrial complex of Ukraine is analysed after 2012-2015 r.r. Certainly basic problems of crediting and suggestions are grounded in relation to the improvement of the credit providing of agricultural commodity producers.
Keywords: bank crediting; credit infrastructure; credit unions; enterprises of agroindustrial complex; favourable crediting; government control